Clinical aspects of chronic dyspepsia in postmenopausal women - Walecka, Ewa; Klupińska, Grażyna; Chojnacki, Jan; Nowak, Janusz (Menopause Review/Przegląd Menopauzalny, 2003)
Objectives. Women in the postmenopausal period often suffer from persistent dyspeptic symptoms such as pain in epigastrium, heartburn or nausea. Part of them are infected with Helicobacter pylori but eradication of bacteria does not always eliminate complaints. Therefore, it has been suggested that dyspepsia might be caused by estrogen deficiency. The aim of the study was to determine the relationship between signs and symptoms of chronic dyspepsia and hormone activity in women. Materials and Methods. The study was performed in 84 women aged 49-62 in which, after excluding other signs and symptoms, dyspepsia occurred for the first time in the period of menopause. The following factors were evaluated: the character of signs and symptoms, the degree of gastric inflammatory changes (according to Sydney System), 17-b-estradiol concentration in blood serum (immunoenzymatic method) and intensity of Helicobacter pylori infection (urea breath test -UBT-13C). In H. pylori infected patients (group I) 7-day antibacterial treatment (omeprazole, amoxicillin, clarithromycin omeprazole at a dose of 2 x 20 mg, amoxicillin – 2 x 1 000 mg and clarithromycin – 2 x 500 mg) was carried out. In patients without H. pylori infection (group II) hormone replacement therapy (HRT) was used (transdermal system with the release of 0.05 mg estradiol/24 h and the oral dose of 5 mg medroxyprogesterone from day 16 to 25 of the menstrual cycle). The degree of treatment effectiveness was evaluated after 12 and 24 weeks. Results. Eradication of H. pylori was obtained in 34 (75.5%) patients, regression of dyspeptic signs and symptoms in 16 (35.5%) women after 12 weeks, and the decrease in dyspepsia intensity (partial improvement) in 11 women (24.4%). In group II complications subsided in 12 women (414%) after 12 weeks, and in 22 (75.8%) after 24 weeks of HRT. Only in 2 patients no alleviation of dyspeptic signs and symptoms was achieved. In the endoscopic assessment after 24 weeks of hormonal therapy, beneficial changes in gastric mucosa were observed. Conclusions. 1. Dyspeptic changes in women can be caused by estrogen deficiency. 2. Hormone replacement therapy can be used as one of the methods of combined treatment in postmenopausal women with chronic dyspepsia.